2015
DOI: 10.1042/bsr20150073
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of mitochondrial transcription factor A (Tfam) expression during skeletal muscle cell differentiation

Abstract: The present study highlights the transcriptional and post-transcriptional regulation of mitochondrial transcription factor A (Tfam) during myogenesis and the relationship this has with the increase in mitochondrial content during differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 26 publications
4
23
0
Order By: Relevance
“…, Collu‐Marchese et al . ), appears also as a plausible molecular explanation for the beneficial adaptations observed in LHTLH vs. LHTL vs. LLTL.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…, Collu‐Marchese et al . ), appears also as a plausible molecular explanation for the beneficial adaptations observed in LHTLH vs. LHTL vs. LLTL.…”
Section: Discussionmentioning
confidence: 87%
“…exercise mode, frequency and duration) between studies might be responsible for these discrepant findings. In summary, the increase in PGC-1a and TFAM measured after intervention in LHTLH, for which mRNA expression predicts protein levels quite well (Handschin et al 2003, Collu-Marchese et al 2015, appears also as a plausible molecular explanation for the beneficial adaptations observed in LHTLH vs. LHTL vs. LLTL.…”
Section: Metabolic Phenotypementioning
confidence: 81%
“…In addition, there creates a ATP deprivation in the cells with increase in AMP:ATP ratio. All these events lead to activation of AMPK, a energy sensor of the body, which upon phosphorylation restores the ATP level by phosphorylating peroxisome proliferator activated receptor γ-coactivator 1α (PGC-1α), a crucial regulator of mitochondrial biogenesis (Wengong et al 2003;Collu-Marchese et al 2015;Guadalupe-Grau et al 2017). Activated PGC-1 allows mitochondria to get adapted to the stress condition imposed by increased energy expenditure, as observed in exercise, thereby maintaining them in functional state.…”
Section: Resultsmentioning
confidence: 99%
“…The role of TFAM in skeletal muscle has been highlighted by muscle-specific loss-of-function studies, which have identified this protein as a required factor for maintaining normal mitochondrial respiratory chain function and muscle strength [151,154]. In skeletal muscle cells, the protein expression of TFAM and its localization to the mitochondrial matrix correlates well with the expression of mtDNA-encoded genes [157], a relationship which holds true following both chronic muscle activity and inactivity [131,134]. Increased Tfam gene expression in muscle has been reported following a single acute session of endurance exercise in both rodent and humans [158][159][160], which is not surprising since TFAM expression is regulated by PGC-1α [161], which is robustly responsive to exercise.…”
Section: Mitochondrial Transcription Factor Amentioning
confidence: 99%